2013
DOI: 10.1177/0013161x13505289
|View full text |Cite
|
Sign up to set email alerts
|

For Grades or Money? Charter School Failure in North Carolina

Abstract: Purpose: Charter schools are unique public schools in part because this type of school can close if it fails to meet objectives set forth by the chartering body that approved it. Thus far, however, little research has been conducted into the causes of charter school closures. In this article, we examine charter school accountability. Research Design: We consider four types of accountability to guide our event history analysis of environmental influences that affect charter school closures in North Carolina. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 42 publications
1
26
2
Order By: Relevance
“…However, although many closed due to financial issues, most of those schools were underperforming when compared to other TCS. Paino et al (2014) found that reading scores, but not math scores, are significant predictors of closures. As a reading scores increase, the likelihood that it will close decreases.…”
Section: The Effects Of Tcs and Tps Closure On Studentsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, although many closed due to financial issues, most of those schools were underperforming when compared to other TCS. Paino et al (2014) found that reading scores, but not math scores, are significant predictors of closures. As a reading scores increase, the likelihood that it will close decreases.…”
Section: The Effects Of Tcs and Tps Closure On Studentsmentioning
confidence: 88%
“…Paino, Renzulli, Boylan and Bradley (2014) conducted a mixed-methods analysis that explored how "macro" and "micro-level processes" that affect TCS closure in North Carolina (p. 500). Using event history analysis, Paino et al (2014) found that a poor financial condition increased the likelihood that a TCS would close, while market and bureaucratic accountability has less of an effect. They found that nearly 63% of closures were due to financial reasons followed by 29% for mismanagement.…”
Section: The Effects Of Tcs and Tps Closure On Studentsmentioning
confidence: 99%
“…The available evidence, however, suggests that accountability and competition often do not function in practice as they are presented in theory (Bulkley, 2001;Paino, Renzulli, Boylan, & Bradley, 2014;Rotherham, 2005). For example, on the issue of accountability, Crew and Anderson (2003), in their study of 103 charter schools in Florida, found that state law required charter schools to produce annual reports that contained information on school finances, faculty and staff, and the attainment of performance goals.…”
Section: Theory Vs Reality In the Literaturementioning
confidence: 99%
“…In terms of the former, it is important to note that legal requirements for accountability vary greatly across political contexts (NACSA, 2015a;Vergari, 2001). 3 Relatedly, some scholars working on charter schools have emphasized four dimensions of accountability: performance (based, e.g., on academic outcomes), market (based on the provision of a distinct service to the community served), bureaucratic (based on compliance with relevant rules and regulations), and financial (based on acceptable use of public tax dollars) (Paino et al, 2014).…”
Section: Theory Vs Reality In the Literaturementioning
confidence: 99%
See 1 more Smart Citation